National commitment to agricultural technology development in Africa - Blackie, Malcolm (Technical Centre for Agricultural and Rural Cooperation, 1993)
Malcolm Blackie works as a field scientist for the Rockefeller Foundation, supporting agricultural research in southern Africa. He started his career as an extension officer in the Zimbabwe government and, before joining the Foundation, was Dean of...